Research progress on distribution and exposure risk of microbial aerosols in animal houses - Lou, Cheng; Bai, Yu; Chai, Tongjie; Yu, Hui; Lin, Tuorong; Hu, Guangming; Guan, Yuling; Wu, Bo (Frontiers in Veterinary Science, 2022)
Environmental aerosols in animal houses are closely related to the productive performance and health level of animals living in the houses. Preferable housing environments can improve animal welfare and production efficiency, so it is necessary to monitor and study these environments. In recent years, there have been many large-scale outbreaks of respiratory diseases related to biological aerosols, especially the novel coronavirus that has been sweeping the world. This has attracted much attention to the mode of aerosol transmission. With the rapid development of large-scale and intensive breeding, microbial aerosols have gradually become the main factor of environmental pollution in animal houses. They not only lead to a large-scale outbreak of infectious diseases, but they also have a certain impact on the health of animals and employees in the houses and increase the difficulty of prevention and control of animal-borne diseases. This paper reviews the distribution, harm, and control measures of microbial aerosols in animal house environments in order to improve people's understanding of them.